Newcastle disease virus activated human peripheral blood mononuclear cells and their use in cancer therapy. - Mohammed Alitheen, Noorjahan Banu; Lam, Han Yuen; Yusoff, Khatijah; Abd Aziz, Suraini; Keong, Yeap Swee (2010)

(untitled)
This invention provides a method for immune activation of human peripheral blood mononuclear cells (PBMC) by treatment with immunogens derived from New Castle Disease virus (NDV). The invention describes a method of activation of PBMC by NDV, the activated PBMCs produced by the inventive method as well as pharmaceutical compositions and vaccines comprising the same. Further embodiments of the invention relate to the use of NDV derived immunogens and the inventive activated PBMCs in immunetheraphy of proliferative diseases - such as cancer. The invention finally provides a method for killing target cells, preferably cancer cells, by co-culturing the target cells together with the inventive activated PBMCs.